2019
DOI: 10.32839/2304-5809/2019-6-70-51
|View full text |Cite
|
Sign up to set email alerts
|

Russia – Ukraine: An Interstate Armed Conflict of the Neocolonial Type

Abstract: Київський національний університет імені Тараса Шевченка рОсія-уКрАїнА: міжДержАВний збрОйний КОнФліКт неОКОлОніАльнОГО тиПу Анотація. Аналізується збройний конфлікт в Україні на сучасному етапі. Автори розглядають специфіку міждержавних конфліктів у постколоніальному світі та розкривають сутність процесу конфліктизації. Специфіка конфліктизації міждержавних відносин в епоху глобалізації полягає в тому, що це явище стає транснаціональним і планетарним за своєю природою. Збройне протистояння на території Україн… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Awareness of the unresolved problems of Ukrainian design education has shifted the vector of domestic scientific developments from the analysis of these problems (Dyachenko, 2021;Averianova & Gook, 2021) to an attempt to provide specific advice on how to solve them and improve the overall efficiency of the educational process (Fursa, 2020;Kozak et al, 2020;Bazyl et al, 2021) The problem of transforming the design education system should not be underestimated. Precisely because its beneficiaries are professionals who, following current trends, dictate future trends and styles, design education must be flexible and mobile in terms of adaptation, both segmental and global.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Awareness of the unresolved problems of Ukrainian design education has shifted the vector of domestic scientific developments from the analysis of these problems (Dyachenko, 2021;Averianova & Gook, 2021) to an attempt to provide specific advice on how to solve them and improve the overall efficiency of the educational process (Fursa, 2020;Kozak et al, 2020;Bazyl et al, 2021) The problem of transforming the design education system should not be underestimated. Precisely because its beneficiaries are professionals who, following current trends, dictate future trends and styles, design education must be flexible and mobile in terms of adaptation, both segmental and global.…”
Section: Discussionmentioning
confidence: 99%
“…Among its pressing problems are: an outdated methodological apparatus; a mismatch between market demands and the content of curricula; insufficient practical training of graduates (Dyachenko, 2021). Averianova and Gook (2021) also add to the above the lack of special artistic training for students, the dismissal of academic staff without academic degrees but with real practical experience. Along with the statement of existing problems, Dyachenko (2021) notes that the active development of non-formal design education, despite its inherent shortcomings, partially solves these problems, so one should not underestimate the possibility of cooperation between higher education institutions and its informal link.…”
Section: Some Aspects Of Design Education In Terms Of Scientific Rese...mentioning
confidence: 99%
“…It can be concluded that none of these options can be implemented in Ukraine, as the country is at war with Russia, which is seeking to occupy Ukrainian territories. The situation in Ukraine with the language conflict is unique, where every citizen can choose the language in which they are more comfortable communicating, but in the national discourse it is vital that the only state language, Ukrainian, is functional as the principal means of mass communication (Averyanova & Voropaeva, 2021). This situation has been observed throughout the entire period of Ukraine's development, where language is the main element of the nation.…”
Section: Language As An Indicator Of Territorial Boundariesmentioning
confidence: 99%
“…The language education and the language component have become crucial factors in countering hybrid threats in Ukraine. As Ukraine faces ongoing challenges, including external aggression and attempts at cultural assimilation, understanding the role of language in countering these threats becomes imperative (Averianova and Voropayeva 2019). The Russian Empire and later the Soviet Union employed various strategies to suppress the Ukrainian language and promote Russian as the dominant language.…”
Section: Literature Reviewmentioning
confidence: 99%